PERBANDINGAN ANTARA CONTINUOUS TRAINING DAN INTERVAL TRAINING TERHADAP PENINGKATAN VO2 MAX PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PADJADJARAN - Arjun Salahuddin; Harry E. Saroinsong; Achmad Hussein S. Kartamihardja (PAIFORI, 2020)
Interval training and continuous training are two models of physical exercise that often used to increase VO2 max. Until now there is no data available, which model is better in the increasing the VO2 max. The aim of this study is to compare the capability between Interval training and continuous training models in increasing the VO2 max. The study was cohort study. Sample of the study are 30 students of the Faculty of Medicine of Universitas Padjadjaran that is 19-24 years old (average 21,7 ± 1,371 years old). Cooper-test method was used to measure the VO2 max where sample are running for 12 minutes in 400 meters running track. The result of Study shows that Interval training increased the VO2 max in the range of 2,64 to 5,06 mL/kg.minutes (average 3,077 ± 0,675 mL/kg.minutes) otherwise continuous training increased the VO2 max in the range of 1,16 to 3,19 mL/kg.minutes (average 2,465 ± 0,611 mL/kg.minutes). The conclusion is that Interval training can increase the VO2 max better than continuous training.